2018
DOI: 10.1371/journal.pone.0199464
|View full text |Cite
|
Sign up to set email alerts
|

Grain zinc concentrations differ among Brazilian wheat genotypes and respond to zinc and nitrogen supply

Abstract: The combined application of nitrogen (N) and zinc (Zn) fertilizers is a promising agronomic strategy for the biofortification of wheat grain with Zn for human nutrition. A glasshouse experiment was carried out to assess the effects of supplying N on the uptake, translocation and accumulation of Zn in tissues of two wheat genotypes (Quartzo and BRS Parrudo) with contrasting potential for grain Zn biofortification. Winter wheat genotypes were grown to maturity in 5 cm diameter, 100 cm length tubes filled with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…A similar relationship between straw Zn content and grain Zn content was shown by Al-Othman et al [107]. Although Zn translocation from root to shoot following Zn uptake by the root is affected by many factors [114], it seems that adequate N supply was the reason for the greatest Zn accumulation in wheat grain in all fields in the present study, as suggested by other authors [115,116]. The particularly low straw Zn content in Experiment I was probably related to the low Zn abundance in the soil (Table 6).…”
Section: Wheat Grain and Strawsupporting
confidence: 91%
“…A similar relationship between straw Zn content and grain Zn content was shown by Al-Othman et al [107]. Although Zn translocation from root to shoot following Zn uptake by the root is affected by many factors [114], it seems that adequate N supply was the reason for the greatest Zn accumulation in wheat grain in all fields in the present study, as suggested by other authors [115,116]. The particularly low straw Zn content in Experiment I was probably related to the low Zn abundance in the soil (Table 6).…”
Section: Wheat Grain and Strawsupporting
confidence: 91%
“…(2011a, 2011b) and Pascoalino et al. (2018) under glasshouse conditions. Other authors have shown that N fertilization is important in uptake and accumulation of Zn in grains where it co‐localizes as proteins with Zn in the embryo and aleurone layers (Cakmak et al., 2010a; Erenoglu, Kutman, Ceylan, Yildiz, & Cakmak, 2011; Ozturk et al., 2009).…”
Section: Discussionmentioning
confidence: 93%
“…The application of N fertilizers had been shown to increase grain Zn concentration following foliar Zn fertilizer applications in wheat ( Triticum aestivum L.; Kutman, Yildiz, & Cakmak, 2011a; 2011b); and rice ( Oryza sativa L.; Jaksomsak, Rerkasem, & Prom‐u‐thai, 2017) grown under glasshouse conditions. While these studies revealed that co‐application of N and Zn fertilizers may be a promising strategy for the agronomic biofortification of cereal grains, there is limited information from field conditions (Pascoalino et al., 2018) on crops more commonly grown in SSA. Conversely, yield increases resulting from N fertilizer have also been reported to dilute or marginally increase grain micronutrient concentrations (Alloway, 2008; Fan et al., 2008; Garvin, Welch, & Finley, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and mapping of molecular markers for quantitative trait loci (QTL) for grain Zn can facilitate screening for increased grain Zn concentration, and such traits can be easily captured using marker assisted selection (Rawat et al, 2009; Tiwari et al, 2010). However, genetic biofortification is possible only if a broad genetic variability is identified for a given trait (Pascoalino et al, 2018). In practice, this may be achieved by identifying wheat cultivars that grow well in soils with low concentrations of plant‐available Zn (Gomez‐Coronado et al, 2016).…”
Section: Capitalising On Genetic Diversity For Zn Biofortificationmentioning
confidence: 99%